2014
DOI: 10.1111/ijn.12368
|View full text |Cite
|
Sign up to set email alerts
|

Much to be desired in self‐management of patients with adrenal insufficiency

Abstract: We assessed self-management in patients with adrenal insufficiency and patient-related factors that affect self-management. A self-report questionnaire was developed to assess self-management. The questionnaire contained three main topics, including: (i) medication adherence; (ii) anticipated measures; and (iii) dose adaptation during medical emergencies. Sixty per cent of the patients (n = 116) completed the questionnaire. The score for the medication adherence was 3.5 out of 4. The score for anticipated meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Calero and Padilha (2014), in a review about the encouragement of therapeutic education of chronic patients, highlights the importance of the support of all disciplines to strengthen the patient's education. They emphasize the role of education as treatment and reinforce that, in regards to chronic patients, it is not about the cure but about teaching self-care, a perspective ratified by other studies (Repping-Wuts, 2013;Van Eck, et al, 2016). The The role of interdisciplinary work is also highlighted by several studies (Elshimy, et al, 2020;Rathbun, et al,2020;Munir, et al, 2021;Huecker, Bhutta & Dominique, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Calero and Padilha (2014), in a review about the encouragement of therapeutic education of chronic patients, highlights the importance of the support of all disciplines to strengthen the patient's education. They emphasize the role of education as treatment and reinforce that, in regards to chronic patients, it is not about the cure but about teaching self-care, a perspective ratified by other studies (Repping-Wuts, 2013;Van Eck, et al, 2016). The The role of interdisciplinary work is also highlighted by several studies (Elshimy, et al, 2020;Rathbun, et al,2020;Munir, et al, 2021;Huecker, Bhutta & Dominique, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…So far, there is only sparse data on the patients' view of their health care situation [6,10,12,16], and hardly any information on AI patients' knowledge of their disease. Aim of the present study was to assess AI patients' knowledge and special needs for patient education through a multiple choice question (MCQ)-based survey and to compare the results with physician's expertise.…”
Section: Limited Patients' Knowledge Of Their Form Of Adrenal Insuffimentioning
confidence: 99%
“…Detailed information is a cornerstone of patient education and treatment in AI [5]; affected individuals should be empowered to self-treatment and adequate dose adjustment to reduce morbidity and mortality [6]. Accordingly, it has been recommended that every AI patient has an emergency kit [2,7,8] as well as an emergency ID [9].…”
mentioning
confidence: 99%
“…Several studies found that 26% – 38% of patients with AI did not adjust their glucocorticoid dose for “sick days” ( 22 , 27 31 ) and only 60% of patients carried a medical-alert ID ( 28 , 29 ). Approximately 70% of patients had an emergency hydrocortisone injection kit ( 5 , 15 ) but only 12% managed to self-inject when they experienced an adrenal crisis ( 15 ), while only 19% were trained to self-inject ( 5 ).…”
Section: Introduction: Self-management For Patients With Adrenal Insu...mentioning
confidence: 99%